Increasing Student Activity And Student Achievement In Pkn Lesson Through Ctl Learning (Contextual Teaching And Learning) At The Fifth Grade Students Of Sd Negeri 09 Parit Kecamatan Sungai Apit Kabupaten Siak - Rauzi Rauzi (Fakultas Sastra Universitas Ekasakti, 2018)
The students achievement of learning civics in SD Negeri No. 09 Parit Kecamatan Sungai Siak Apit Kabupaten Sungai Siak is still below the minimum completeness criteria specified.This is due in teaching learning process, the teacher has the ability to appropriate learning models, so that students are less motivated.Efforts are being made to overcome these problems is through learning model CTL.The purpose of this study is to improve student learning outcomes in learning Civics. The type of research is Classroom Action Research (PTK), with the subject of research teachers and students of class V as many as 28 people, male as many as 16 people and women as many as 12 people.The research was conducted in SD Negeri No.09 Parit Kecamatan Sungai Apit Kabupaten Siak, which consisted of two cycles of two meetings in the first cycle and two meetings in the second cycle.This research uses CTL learning model as its research object.Instrumentation used in this research is observation sheet and test which analyzed with percentage. The results showed that the students' learning outcomes in the first cycle of meeting I was 55.71% and in cycle I in meeting II was 65%.In the second cycle of meeting I is 80.36% and on second cycle of meeting II is 85%. The implementation of Civic learning using CTL learning model in cycle I have not been able to improve student learning outcomes. In cycle II the use of CTL learning can improve student learning outcomes in accordance with both criteria. Thus, learning Civics with learning models of CTL can improve student learning outcomes well.